Surface coating of ceria nanostructures for high-temperature oxidation protection. (13th April 2018) - Aadhavan, R; Bhanuchandar, S; Babu, K Suresh
Abstract: Stainless steels are used in high-temperature structural applications but suffer from degradation at an elevated temperature of operation due to thermal stress which leads to spallation. Ceria coating over chromium containing alloys induces protective chromia layer formation at alloy/ceria interface thereby preventing oxidative degradation. In the present work, three metals of differing elemental composition, namely, AISI 304, AISI 410, and Inconel 600 were tested for high-temperature stability in the presence and absence of ceria coating. Nanoceria was used as the target to deposit the coating through electron beam physical vapor deposition method. After isothermal oxidation at 1243 K for 24 h, Ceria coated AISI 304 and Inconel 600 exhibited a reduced rate of oxidation by 4 and 1 orders, respectively, in comparison with the base alloy. The formation of spinel structure was found to be lowered in the presence of ceria due to the reduced migration of cations from the alloy.